Utilizing nanomaterials to functionalize the Tikoua extract as a powerful green anti-corrosion inhibitor for carbon steel - Rania Farouq; Eman Hamdy; Moustafa M. S. Abbassy; H. A. Farag (Journal of Petroleum Exploration and Production Technology)
Abstract The employment of toxic, hazardous, and environmentally damaging inhibitors poses a major risk to both the environment and public health. Recently, there has been a lot of interest in using phytochemical-rich natural extracts as environmentally friendly corrosion inhibitors and expensive, non-corrosive coating materials to safeguard metallic structures of significant commercial value. Functionalization of the tikoua extract with nanomaterials such as ZnO, CuO, and Sodium lauryl sulfate (SLS), and their composites was studied as a corrosion inhibitor of carbon steel in acid corrosion media. Weight loss measurements, scanning electron microscope, and atomic absorption spectroscopy have been used to explore the inhibitory effects of the synthesized composites. The components of the synthesized composite inhibitors were characterized using a GC-MS analysis which identified major phytochemical constituents, such as octacosane, vitamin E, and α-sitosterol, that contribute to corrosion inhibition. Particle size analysis showed nanocomposites in the 204–416 nm range. SEM confirmed substantial surface protection, especially with ZnO. Multiple measurements revealed that these composites adsorb tightly on the carbon steel surface to prevent corrosion in carbon steel. It was observed that the inhibition efficiency increases as the plant extract concentration rises to 53% at 1000 ppm. Results show that ficus extract inhibited the acid corrosion of carbon steel and the inhibition performance was enhanced in the presence of nanoparticles. It was found that ZnO gave the best results. By using 100 ppm ZnO Nanomaterial with plant extract the inhibition efficiency reaches 87.43%. The purpose of this paper is to clarify how effective plant extract with nanomaterials is at protecting steel from acidic environments.